The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1001/jamaoto.2020.0014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Prognostic Value of FDG PET/CT Parameters for Patients With Surgically Treated Head and Neck Cancer

Abstract: IMPORTANCEHead and neck squamous cell cancer (HNSCC) represents the seventh most frequent cancer worldwide. More than half of the patients diagnosed with HNSCC are treated with primary surgery.OBJECTIVE To report the available evidence on the value of quantitative parameters of fluorodeoxyglucose F 18-labeled positron emission tomography and computed tomography (FDG-PET/CT) performed before surgical treatment of HNSCC to estimate overall survival (OS), disease-free survival (DFS), and distant metastasis (DM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 71 publications
3
23
1
1
Order By: Relevance
“…With SUV max as the most commonly measured factor, they confirmed that the volumetric parameters (MTV, TLG) presented a higher prognostic value for several primary endpoints. Six studies focused on the oral cavity with a range of 28-148 participants (median 75.5) and the results were in line with our data [62].…”
Section: Discussionsupporting
confidence: 87%
“…With SUV max as the most commonly measured factor, they confirmed that the volumetric parameters (MTV, TLG) presented a higher prognostic value for several primary endpoints. Six studies focused on the oral cavity with a range of 28-148 participants (median 75.5) and the results were in line with our data [62].…”
Section: Discussionsupporting
confidence: 87%
“…Finally, recent systematic reviews (one of them including also a meta-analytic analysis) evaluated the relationship between semiquantitative metabolic parameters and outcomes of patients with HNC. These data demonstrated that higher pre-treatment MTV is linked to worse OS, PSF, and locoregional control ( 50 , 51 ).…”
Section: Role Of Molecular Imaging In Researchmentioning
confidence: 84%
“…Computed tomography is commonly used in HNSCC cancer as a part of clinical management (diagnosis, staging, RT planning), and a multitude of studies have used CT radiomics for prognostication [26]. Leger et al compared CT-derived radiomic features from baseline and week 2 scans for predicting locoregional tumor control in patients with HNSCC.…”
Section: Discussionmentioning
confidence: 99%